Inovasi Penggunaan AI (Artificial Intelligenc) Dalam Pembelajaran Pendidikan Agama Islam di MAN 4 Persiapan Kota Medan - Siti Hawa Lubis; anri naldi; Reskina Reskina; Adlan Fauzi Lubis; Nurhayati Nurhayati (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2023)
In this digital era, innovation in the use of AI (Artificial Intelligence) in learning is needed. Islamic religious education teachers must be able to innovate learning. The purpose of the study was to analyze the innovation and constraints of the use of Artificial Intelligence in learning Islamic Religious Education at MAN 4 Preparation of Medan City. The research method is qualitative with a phenomenological approach. The results of this study found innovation in the use of Artificial Intelligence at MAN 4 Preparation of Medan City using the Madrasah e-learning application. The advantages of this application Through madrasah e-learning, teachers and students can conduct integrated video conferences with students and stakeholders without time limits and free of charge. In addition, daily assessments, quizzes, end-of-semester assessments can be done through computer-based exams which are directly processed into report cards. The obstacles faced in mastering the e-learning application of Madrasah 1). Weak mastery of technology by teachers and students 2). Some students still do not have a handphone or computer 3). The lack of socialization of the use of e-learning applications to teachers and students.